Report on industrial attachment with Pfizer Nutrition Singapore Pte Ltd - Tay, Grace Sin Yee (2014)
This report provides a summary of the training experiences received during the Industrial Attachment with Pfizer Nutrition Singapore Pte Ltd from 9th January 2012 to 9th June 2012. It includes the various learning processes from the duties and projects, which were assigned. The first part of the report covers a brief introduction to the background of the company and the scope of the report. The next part of the report will be covering two routine tests done during the attachment period. The first test is the determination of the solubility in raw materials. It is to ensure efficiency in manufacturing process in an attempt to maintain the quality if products. The second test is the determination of scorched particles in raw materials. The presence of scorched particles may indicate problems with the cleanliness of the drier and/or excessive high drying temperature. The lesser the number of particles, the better the raw material is. The next part of the report will elaborate on two major projects assignes during the course of the attachment period. One of the projects is to create trend charts to monitor the process performance which is done by checking whether the different nutrients of the finished product fall within the control limits. The other project, motion and transportation, is to reduce the movements when carrying out test so that unnecessary bending, reaching or walking during a test can be greatly reduced.